Serotonin and early life stress interact to shape brain architecture and anxious avoidant behavior – a TPH2 imaging genetics approach. Issue 14 (28th October 2021) - Liu, Congcong; Xu, Lei; Li, Jialin; Zhou, Feng; Yang, Xi; Zheng, Xiaoxiao; Fu, Meina; Li, Keshuang; Sindermann, Cornelia; Montag, Christian; Ma, Yina; Scheele, Dirk; et al.
Abstract: Background: Early life stress has been associated with emotional dysregulations and altered architecture of limbic-prefrontal brain systems engaged in emotional processing. Serotonin regulates both, developmental and experience-dependent neuroplasticity in these circuits. Central serotonergic biosynthesis rates are regulated by Tryptophan hydroxylase 2 ( TPH2 ) and transgenic animal models suggest that TPH2 -gene associated differences in serotonergic signaling mediate the impact of aversive early life experiences on a phenotype characterized by anxious avoidance. Methods: The present study employed an imaging genetics approach that capitalized on individual differences in a TPH2 polymorphism (703G/T; rs4570625) to determine whether differences in serotonergic signaling modulate the effects of early life stress on brain structure and function and punishment sensitivity in humans ( n = 252). Results: Higher maltreatment exposure before the age of 16 was associated with increased gray matter volumes in a circuitry spanning thalamic-limbic-prefrontal regions and decreased intrinsic communication in limbic-prefrontal circuits selectively in TT carriers. In an independent replication sample, associations between higher early life stress and increased frontal volumes in TT carriers were confirmed. On the phenotype level, the genotype moderated the association between higher early life stress exposure and higher punishment sensitivity. In TT carriers, the association between higher early life stress exposure and punishment sensitivity was critically mediated by increased thalamic-limbic-prefrontal volumes. Conclusions: The present findings suggest that early life stress shapes the neural organization of the limbic-prefrontal circuits in interaction with individual variations in the TPH2 gene to promote a phenotype characterized by facilitated threat avoidance, thus promoting early adaptation to an adverse environment.